Glomerulonephritis and Nephrotic Syndrome - Rath, Thomas (IntechOpen, 2019)
Chronic kidney disease is a worldwide disease affecting up to 4% of the population. In many cases, glomerulonephritis is the underlying disease leading to kidney failure. One hallmark of glomerulonephritis is proteinuria, which may in its most severe form lead to nephrotic syndrome. In seven chapters, this book puts light on different aspects related to the pathophysiology and clinical aspects of glomerulonephritis. In addition, chapters dealing with the importance of biomarkers in patients with glomerulonephritis will be beneficial for the open-minded reader. Nevertheless, new insights in renal rehabilitation in patients with chronic kidney disease will be provided.